المعايير الدولية لإدارة أمن المعلومات - هدى, بن محمد; ابتسام, طوبال; نجاة, كورتل (جامعة الوادي university of eloued, 2023)
يهدف هذا البحث إلى التعرف على أمن المعلومات، وتسليط الضوء على مختلف المعايير الدولية المقبولة من أغلب الدول والمنظمات لإدارة أمن المعلومات، ونخص بالذكر معيار ISO / IEC 27001، ذلك لأن المنظمات الحائزة على هذه المعايير ستعزز من مكانتها على المستوى المحلي والإقليمي وسيشكل حصولها على هذه المعايير دافعا قويا للاستمرار في تطوير خدماتها ومنتجاتها وفق أعلى وأفضل المعايير والأنظمة الدولية للرفع من ثقة المواطنين والعملاء والمستثمرين في كافة الأنشطة والعمليات التي تقوم بها. This research aims to identify information security, and to shed light on the various international standards accepted by most countries and organizations for managing information security, in particular the ISO / IEC 27001 standard, because organizations that have these standards will enhance their position at the local and regional level and will constitute their access to these standards. Standards are a strong motivation to continue to develop its services and products in accordance with the highest and best international standards and regulations to raise the confidence of citizens, customers and investors in all activities and operations carried out by them
مقال
Keywords: أمن المعلومات ; عائلة معايير ISO / IEC 27000 ; معيار ISO / IEC 27001